2019
DOI: 10.1093/biolre/ioz081
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic impacts of endocrine disruptors on female reproduction across generations†

Abstract: Humans and animals are repeatedly exposed to endocrine disruptors, many of which are ubiquitous in the environment. Endocrine disruptors interfere with hormone action; thus, causing non-monotonic dose responses that are atypical of standard toxicant exposures. The female reproductive system is particularly susceptible to the effects of endocrine disruptors. Likewise, exposures to endocrine disruptors during developmental periods are particularly concerning because programming during development can be adversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 114 publications
1
38
0
1
Order By: Relevance
“…In rhesus macaques, administration of ethanol to simulate binge drinking can compromise oocyte quality, even after the treatment is terminated (VandeVoort et al, 2014). Exposure to environmental endocrine disruptors can impact meiosis and oocyte quality and have multi‐generational and transgenerational effects in the ovary (Rattan & Flaws, 2019). Maternal diets deemed unhealthy can lead to mitochondrial dysfunction, inflammation, changes in ER stress and UPR related gene expression ( Atf4, Xbp1s, Hspa1a, Hapa1b ) and reduced developmental competence in ovulated oocytes compared to control litter mates (Boudoures et al, 2017; Ruebel et al, 2017; Snider & Wood, 2019; L. L. Wu et al, 2015).…”
Section: Environmental Factors Impacting Long‐term Maternal Effectsmentioning
confidence: 99%
“…In rhesus macaques, administration of ethanol to simulate binge drinking can compromise oocyte quality, even after the treatment is terminated (VandeVoort et al, 2014). Exposure to environmental endocrine disruptors can impact meiosis and oocyte quality and have multi‐generational and transgenerational effects in the ovary (Rattan & Flaws, 2019). Maternal diets deemed unhealthy can lead to mitochondrial dysfunction, inflammation, changes in ER stress and UPR related gene expression ( Atf4, Xbp1s, Hspa1a, Hapa1b ) and reduced developmental competence in ovulated oocytes compared to control litter mates (Boudoures et al, 2017; Ruebel et al, 2017; Snider & Wood, 2019; L. L. Wu et al, 2015).…”
Section: Environmental Factors Impacting Long‐term Maternal Effectsmentioning
confidence: 99%
“…In addition, epigenetic stressors including endocrine-disrupting chemicals, alcohol and nicotine abuse, can cause intergenerational reproductive health and metabolism effects [95][96][97][98][99][100]. In the context of endocrine-disrupting chemicals, transgenerational effects on brain, behavior, and reproduction have been documented [95,[101][102][103]. For example, in one of the earliest studies, which reported the paternal effect, it was demonstrated that the exposure of pregnant rats to high levels of vinclozolin during fetal gonadal development induced decreased sperm number and motility in F1, F2, F3, and F4 generations, with 8% of males developing infertility [95].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…EDCs can act on sex-steroid hormone receptors, so during critical developmental periods if the fetus is exposed to EDCs, remethylation could occur within the germ cells, and these effects can be observed in subsequent generations [64]. Transgenerational effects, involving the transmission of epigenetic changes in the germline, occur when effects from the endocrine disruptor are observed without direct exposure, or in F3 [65,66]. In contrast, if passed down by the paternal lineage, the epigenetic phenotype becomes transgenerational once expressed in the F2 generation [66].…”
Section: Epigenetic Transgenerational Inheritance Of Endocrine Diseasmentioning
confidence: 99%
“…In contrast, if passed down by the paternal lineage, the epigenetic phenotype becomes transgenerational once expressed in the F2 generation [66]. During adult life, if the F0 generation is exposed to endocrine disruptors, preconceptionally the F1 generation is being directly exposed [65]. Multigenerational effects are when any effects of the endocrine disruptor are observed in the F1 and F2 generations [65].…”
Section: Epigenetic Transgenerational Inheritance Of Endocrine Diseasmentioning
confidence: 99%
See 1 more Smart Citation